Standardizing the computerized analysis and modeling of luminescence phenomena: New open-access codes in R and Python - Pagonis, Vasilis; Kitis, George (Radiation measurements, 2022)
In this paper we describe a new initiative for the development of open-access codes in R and Python, to be used for computerized analysis and modeling of luminescence phenomena. The purpose of this broad initiative is to help in the classification, organization and standardization of the computerized analysis and modeling of a wide range of luminescence phenomena. Although a very significant number of such open access codes is already available in the literature, there is a lack of common standardization and homogeneity in the nomenclature and in the codes, which we hope to address. New open-access codes are developed for thermoluminescence (TL), isothermal luminescence (ITL), optically stimulated luminescence (OSL), infrared stimulated luminescence (IRSL), dose response (DR) and time-resolved (TR) signals. In each of these categories, computer codes are currently being developed based on (a) delocalized transitions involving the conduction/valence bands and (b) localized transitions based on proximal interactions between traps and centers. Whenever applicable, additional codes are developed for semi-localized transition models, which are based on a combination of localized and delocalized transitions. While many previously published codes are based on the empirical general order kinetics and on first order kinetics, several of the new codes in R and Python are based on physically meaningful kinetics described by the Lambert W function. During the past decade, the Lambert W function has been shown to describe both thermally and optically stimulated phenomena, as well as the nonlinear dose response of TL/OSL/ESR in dosimetric materials. The paper demonstrates the proposed classification and organization of the codes, which it is hoped will be a useful tool, especially for newcomers to the field of luminescence dosimetry. •A new initiative: development of open-access codes in R and Python.•Codes can be used for computerized analysis and modeling of luminescence phenomena.•Purpose: classification, organization and standardization of computerized analysis.•Open-access codes for TL, ITL, OSL, IRSL, dose response and time-resolved signals.